2009
DOI: 10.1021/ja902716d
|View full text |Cite
|
Sign up to set email alerts
|

Imino-oxy Acetic Acid Dealkylation as Evidence for an Inner-Sphere Alcohol Intermediate in the Reaction Catalyzed by Peptidylglycine α-Hydroxylating Monooxygenase

Abstract: Peptidylglycine α-hydroxylating monooxygenase (PHM, EC 1.14.17.3) catalyzes the stereospecific hydroxylation of a glycyl α-carbon in a reaction that requires O2 and ascorbate. Subsequent dealkylation of the α-hydroxyglycine by another enzyme, peptidylamidoglycolate lyase (PAL. EC 4.3.2.5), yields a bioactive amide and glyoxylate. PHM is a non-coupled, type II dicopper monooxygenase which activates O2 at only a single copper atom, CuM. In this study, the PHM mechanism was probed using a non-natural substrate, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 72 publications
2
19
0
Order By: Relevance
“…For PHM and DβM, the ( A )-->( B ) step is postulated as that effecting H-atom abstraction from a R-H substrate, 6b,13 but other views exist. 14 …”
Section: Introductionmentioning
confidence: 99%
“…For PHM and DβM, the ( A )-->( B ) step is postulated as that effecting H-atom abstraction from a R-H substrate, 6b,13 but other views exist. 14 …”
Section: Introductionmentioning
confidence: 99%
“…Studies of the kinetic mechanism show that the O 2 and the oxidizable substrate only bind after the reduction of enzyme-bound 2Cu(II) to 2Cu(I) by ascorbate 75 . We found that O 2 binds after hippurate or benzyaldehyde iminooxy acetate 76 rendering the O 2 -requirement for cinnamate inactivation perplexing. Either the order of binding for cinnamate is different, requiring O 2 to bind to reduced PHM before cinnamate can bind, or O 2 binding to the reduced PHM–cinnamate complex results in a subtle rearrangement in the active site to facilitate cinnamate attack by the active site nucleophile.…”
Section: Discussionmentioning
confidence: 93%
“…Previous work has established that the addition of the oxidizible substrate occurs after the reduction of enzyme-bound Cu(II) atoms 18e,19. Using ascorbate as the exogenous reductant, Merkler et al 49.…”
Section: Discussionmentioning
confidence: 99%
“…The first step in the catalytic cycle for both enzymes is reduction of the enzyme-bound Cu(II) atoms with an exogenous reductant, most likely ascorbic acid in vivo . Reduction is ping-pong with release of oxidized reductant from E•2Cu(I) followed by binding O 2 or oxidizable substrate to the reduced enzyme 18,19. The dependence of 18 O-kinetic isotope effect on deuteration of the oxidizable substrate for both enzymes indicates that C-H bond cleavage precedes cleavage of the activated O 2 complex, yielding a Cu(II)-hydroperoxo and a substrate-based radical 20.…”
Section: Introductionmentioning
confidence: 99%